Drzwi do pokoju - Kudyba, Wojciech (Colloquia Litteraria, 2011)
Czeslaw Milosz’s poem Późna dojrzałość describes the experience of spiritual breakthrough. His past time hero feels incomplete. Full– time starts for him at the time of “awakening”. However, deep experience of “me” leads eventually beyond ego – towards the relations with others. The protagonist recognizes both a personal value of himself and of the others. It is the dignity of a “child of the King”, it has its source not so much in axiology, as in the ontology. The described spiritual breakthrough does not solve world’s problems, but introduces a new perspective of their understanding. It allows – thanks to a deep experience of hope – to anticipate the future harmony. Internal doors allow the hero to look into something which will become complete at the end of time, yet it now exists in the form of announcement hidden in the structure of reality.